Material and energy flow analysis of craft brewing: A case study at a California microbrewery - Peterson, Scott D.; Amón, Ricardo; Wong, Tony; Spang, Edward S.; Simmons, Christopher W. (Frontiers in Sustainable Food Systems, 2022)
Small breweries have been growing in number and volume share in the US marketplace. Brewing is water- and energy-intensive, especially for small brewers who do not benefit from the same economies of scale as large brewers. A systematic approach to characterizing the water and energy flows in small breweries will help researchers and process owners identify opportunities for efficiency improvement by reducing waste. The information from such analysis yields granular information about where water and energy (electrical and thermal) are embedded into beer. It also contextualizes a small brewery's specific water and energy consumption relative to peer breweries, providing a quantitative basis for decision-making that ultimately impacts economic competitiveness. In the present work, a case study is performed on a microbrewery in northern California. Visualization tools are provided that delineate how water and energy flow through the brewery. Specific electrical energy consumption was 183.7 MJ per US beer barrel (bbl) (1.6 MJ/L) packaged in the first half of 2018, thermal energy 489.4 MJ/bbl (4.2 MJ/L), water 12.8 bbl consumed/bbl (12.8 L/L), and wastewater 10.8 bbl discharged/bbl (10.8 L/L). These specific resource consumptions are placed into context relative to other small breweries. The metrics are high due to general inefficiency relative to peer facilities, reverse economies of scale in small breweries, and associated utility costs impacted by geographic location. Overall utility costs were 26.95 per bbl packaged vs. 16.01 for similar-sized breweries. This analysis sheds light on the virtuous cycle of how reducing one input in the beer-water-energy nexus will often lead to other resources being conserved as well, due to the overlapping nature of their embedment in the final product.